Pemanfaatan Serbuk Batang Kayu Puspa Sebagai Pembuatan Papan Partikel Terhadap Pengujian Impak - Novizal, Novizal; Yuliyanto, Yuliyanto; Rollastin, Boy (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
In order to satisfy the wants and desires of human life, science and technology have advanced quickly. Science and technology are developing in many facets of life. Technological advancements also happen in composite materials, which are still being studied today. Particleboard is a manufactured board created by pressing industrial waste from plantations, forestry, and agriculture together with organic adhesives. Low-quality wood waste products that may contain cellulose and lignin, such as sawdust, twigs, lathing residue, and others, can be used. The PVAc polymer was subjected to temperatures of 90°C, 100°C, and 110°C in this work, which employed a direct experimental method. The parameters used were mesh 10, 20, and 30 with a volume fraction of 60%: 40%, 70%: 30%, and 80%: 20%. In this study, the results of the largest impact strength were found in the volume fraction of 60%:40% on mesh 30 with heating at 90°C for 15 minutes amounting to 16.34 J/m2, and the smallest impact value was found in the volume fraction of 70%:30% on mesh 10 with heating at 100°C amounting to 9.28 J/m2, where these values do not meet the SNI-03-2105-2006 standard for making particle boards.